Experimental Evaluation of the Transport Mechanisms of PoIFN-α in Caco-2 Cells - Liu, Xin; Zheng, Sidi; Qin, Yue; Ding, Wenya; Tu, Yabin; Chen, Xingru; Wu, Yunzhou; Yanhua, Li; Cai, Xuehui (Frontiers in Pharmacology, 2017)
For the development of an efficient intestinal delivery system for PoIFN-α, the understanding of transport mechanisms of which in the intestinal cell is essential. In this study, we investigated the absorption mechanisms of PoIFN-α in intestine cells. Caco-2 cells and fluorescein isothiocyanate-labeled (FITC)-PoIFN-α were used to explore the whole transport process, including endocytosis, intracellular trafficking, exocytosis and transcytosis. Via various techniques, the transport pathways of PoIFN-α in Caco-2 cells and the mechanisms were clarified. Firstly, The endocytosis of PoIFN-α by Caco-2 cells was time, temperature and concentration dependent. And the lipid raft/caveolae endocytosis was the most likely endocytic pathway for PoIFN-α. Secondly, both Golgi apparatus and lysosome were involved in the intracellular trafficking of PoIFN-α. Thirdly, the treatment of indomethacin resulted in a significant decrease of exocytosis of PoIFN-α, indicating the participation of cyclooxygenase. Finally, to evaluate the efficiency of PoIFN-α transport, the transepithelial electrical resistance (TEER) value was measured to investigate the tight junctional integrity of the cell monolayers. The fluorescence microscope results revealed that the transport of PoIFN-α across the Caco-2 cell monolayers was restricted. In conclusion, this study depicts a clear picture of PoIFN-α transport in Caco-2 cells characterized by non-specificity, partial energy-dependency and low transcytosis.